Correlation of Antioxidant Activity and Phytochemical Profile in Brown Rice and Brown Rice Products - Nakornriab, Muntana (Journal of Food Health and Bioenvironmental Science, 2018)
Brown rice and brown rice products (brown rice, germinated brown rice, dry germinated brown rice, germinated brown rice noodle and dry germinated brown rice noodle) were studied for their total phenolic, total flavonoid, γ-aminobutyric acid (GABA) content and antioxidant activity by DPPH and FRAP assay. The results indicate that the brown rice extract shows the highest on total phenolic contents (0.52±0.03 mg GAE/g of fresh weight), followed by germinated brown rice, germinated brown rice noodle, and dry germinated brown rice noodle, respectively. The total flavonoid content is only found in brown rice (0.35±0.03 mg quercetin/100 g sample). In GABA content, the germinate brown rice shows the highest on GABA value (75.02±0.52 mg GABA/g of fresh weight), followed by germinate brown rice noodle, dry germinate brown rice noodle, and brown rice, respectively. Percentage of inhibition and the concentration of sample required for 50% scavenging of the DPPH free radical (IC50) were determined for the antioxidant activity, germinated brown rice shows the highest DPPH (IC50; 27.2±4.3 mg/mL), followed by brown rice, and dry germinated brown rice, respectively. Brown rice shows the highest FRAP (5.95±8.44 mM Fe (II) /g of fresh weight), followed by germinate brown rice, germinate brown rice noodle, and dry germinate brown rice noodle, respectively.